Tinjauan Multidimensi Kinerja Keuangan PT Wahana Ottomitra Multiartha Finance Melalui Pendekatan Rasio Likuiditas, Profitabilitas, Solvabilitas, Dan Aktivitas - Anita Anggraini Safitri; Syamsul Arifin (Jurnal Riset Akuntansi, 2023)
This research aims to determine the financial performance of PT WOM Finance, evaluated through financial ratio analysis for the years 2019-2021. The data analysis method used is qualitative descriptive method, employing the measurement of liquidity, solvency, and profitability ratios. Based on the research findings, the liquidity ratios for the period 2019-2021 can be considered good, as the company is able to meet its short-term obligations. Regarding the solvency ratios for the same period, the company demonstrates positive steps by reducing its use of debt in financing its capital, indicating a good financial stability. However, in terms of profitability ratios for the period 2019-2021, the company has not been able to achieve the desired profits. This is evident from the difficulties encountered in generating profits with each sale.